Assessing the Administration of Micro-Credit to Small Scale Industries in the Upper Denkyira East Municipal Assembly: A Case Study of the Amenfiman Rural Bank Limited - Musah, Abdul-Aziz (2012)
A Thesis Submitted to the Institute of Distance Learning, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Commonwealth Executive Masters in Business Administration, 2011